Pengaruh Latihan Setter Training Ball dan Medicine Ball Terhadap Keterampilan Passing Atas pada Atlet Bola Voli Putri - Rizqi Amalia; Said Junaidi; Nanang Indardi; Gustiana Mega Anggita; Siti Baitul Mukarromah; M. Arif Ali (Indonesian Journal of Kinanthropology (IJOK), 2023)
Background: Overhead pass is one of the important elements in volleyball, implementing good passing can make the game run well too. The purpose of this study was to determine the effect of training with setter training balls and medicine balls on overhead passing skills in female volleyball athletes at the Elang Bahari Tegal Club. Methods: This type of research is an experiment with a pretest-posttest design. The population in this study were all female volleyball athletes from the Elang Bahari Club, totaling 14 athletes. Sampling technique with purposive sampling. The number of sampel used were 10 athletes. The instrument used in this study was the Brady Volleyball Test. Data analysis techniques using the t test. Results: The result of the t test analysis in the setter training ball group t count = 8,353 > t table = 1,812, and the result of the t test in the medicine ball group t count = 6,520 > t table = 1,812. Conclusions: It can be concluded that there is an effect of training with setter training balls and medicine balls on the overhead passing skills of female athletes at the Elang Bahari Tegal club.